Big data storage for a health predictive system - João Rala Cordeiro; Postolache, O. (2018 International Symposium in Sensing and Instrumentation in IoT Era, ISSI 2018, 2018)
When referring to health data processing and management quickly comes across the challenge for storing this kind of information. This article resumes the research for a storage model able to support a baby's multimodal healthcare predictive system, which our team is developing. We have took a structured approach where we define the data characteristics, the systems requirements and most significant operations required to our “business”. Understanding relational and non-relational approaches, and differences between NoSQL database categories we have defined what we consider the best approach for our scenario, is this case a mix of document and extensible record stores. Finally we analyze the different available technologies/platforms on this categories and how they can support our system requirements.